Aplikasi Cek Nutrisi pada Makanan Berbasis Android - Maulida Ayu Fitriani; Andono Pamungkas Warih (UM Purwokerto Press, 2021)
Nutrition is an absolute factor needed by the body in the process of growth and development. However, the general public today is still difficult to maintain nutritional intake in the food consumed every day. Therefore, by utilizing the development of technology on mobile phones that are becoming increasingly smarter with the Android operating system, an application was made to help the public monitor nutritional intake and features that support rearranging their diet. The application was made with the Kotlin programming language using the Android Studio IDE. The model used in application development was the Scrum model. With the stages of determining the product backlog, determining sprint planning, daily scrum, sprint review, and sprint retrospective. The result of this practical work was the Nutrifit application which could make it easier for the general public to monitor the daily nutritional intake needed to keep the body healthy during the pandemic.